Stretchable Parylene-C electrodes enabled by serpentine structures on arbitrary elastomers by silicone rubber adhesive - Bowen Ji; Zhaoqian Xie; Wen Hong; Chunpeng Jiang; Zhejun Guo; Longchun Wang; Xiaolin Wang; Bin Yang; Jingquan Liu (Journal of Materiomics, 2020)
The delicate serpentine structures are widely used in high-performance stretchable electronics over the past decade. The metal interconnects encapsulated in biocompatible polymer Parylene-C film is a superior choice for long-term implantation in vivo, especially as neural interface to acquire electrophysiological signals or apply electrical stimulation. To avoid the physical contact damages from the neural tissues such as the brain or peripheral nerves, serpentine interconnects are utilized as stretchable electrodes and usually bonded to the soft elastomer substrate. The adhesion strength between the serpentine interconnects and the elastomer substrate becomes a considerable issue to ensure reliability and structural integrity. In this paper, the stretchable Parylene-C electrodes can be transfer printed onto arbitrary elastomer substrates by a thin layer of silicone rubber adhesive with low modulus for electrocorticogram (ECoG) recording. Mechanical simulation of serpentine structures consisting of same periodic arcs and different straight segments is investigated by uniaxial stretching. Then, the elastic stretchability of serpentine electrodes is further studied by simulation and experiments. After 5000 repetitive stretching cycles, the electrochemical impedance of microelectrodes remains in steady states. These results prove that the silicone rubber adhesive facilitates the interfacial bonding in the structure of stretchable electrodes as the compliant and reliable neural interface. Keywords: Stretchable Parylene-C electrodes, Serpentine structure, Arbitrary elastomers, Silicone rubber adhesive